二ホンイヌワシの保全科学 : 現状と将来展望について - OGDEN, Rob; FUKUDA, Tomokazu; FUNO, Takayuki; KOMATSU, Mamoru; MAEDA, Taku; MEREDITH, Annna; MIURA, Masaya; NATSUKAWA, Haruki; ONUMA, Manabu; OSAFUNE, Yuki; SAITO, Keisuke; SATO, Yu; et al. (Japanese Journal of Zoo and Wildlife Medicine, 2020)
イヌワシの一亜種であるニホンイヌワシ（Aquila chrysaetos japonica）は，個体数と繁殖状況の現状調査に基づいて，環境省版レッドリストの絶滅危惧種に指定されている。現在，国による保全活動が行われているものの，個体数減少の原因とその改善方法に関する知見は，十分とはいえない。この数十年の間に，日本を含む世界各地において，イヌワシの種の回復に関する多分野にわたる科学的な研究が行われ，本種の保全計画に必要な情報が集められつつある。しかしながら，これらの研究は個別に進められており，学際的なアプローチが充分になされていない。本稿では，生態学，遺伝学，獣医学的健康管理，生息地管理などの，ニホンイヌワシの保全に関する諸研究を総合して概観した。野生および飼育下個体群の現状と傾向を分析し，現在および将来の保全管理の活動を報告し，ニホンイヌワシの生息域内保全および生息域外保全に向けた対策について，統合的な見地から議論した。この総説では，イヌワシの生物学や健康科学に関する国内および海外の専門家グループが，学術的な情報と実用的な解決策の両方を提示した。本稿によって，ニホンイヌワシの数の減少をくいとめるのに必要な情報と技術を提供し，日本における長期的な本種の保全に応用するための枠組みを示すことを目指す。 According to current trends in census size and reproduction, the Japanese golden eagle (Aquila chrysaetos japonica) is at risk of extinction this century, leading the Japanese government to recognize the subspecies as endangered. It is now the focus of national conservation efforts, yet gaps remain in our knowledge regarding the reasons for the observed population decline and how best to improve the situation. Over recent decades, scientific research concerning golden eagle conservation in Japan, and in other parts of the world, has established a multi-disciplinary body of evidence that should support plans for species restoration. However, until now, these strands of research have been largely separate, limiting the potential benefits offered by an inter-disciplinary approach. In this paper, we provide an integrated review of Japanese golden eagle conservation science, including studies of ecology, genetics, veterinary health and habitat management. We assess the status and trends in the wild and captive populations; identify current and future conservation management interventions and discuss the opportunities for taking an integrated approach to Japanese golden eagle conservation science through in-situ and ex-situ viewpoint. This review, prepared by national and international experts in golden eagle biology and health, describes outstanding scientific questions alongside potential practical solutions. It sets out a framework for applied research that will ...